Recurrence and structuring of sequences of transformations 3n + 1 as arguments for confirmation of the collatz hypothesis - Кособуцький, Петро; Каркульовський, Володимир; Kosobutskyy, Petro; Karkulovskyy, Volodymyr (Видавництво Львівської політехніки, 2023)
Показано, що необмеженість підпослідовності непарних чисел не контраргумент порушення гіпотези Коллатца, а універсальна характеристика перетворень натуральних чисел за алгоритмом 3n+1. Встановлений рекурентний зв’язок між параметрами послідовності Коллатца перетворень довільної пари натуральних чисел n і 2n .

It is shown that infinites of the subsequence of odd numbers is not a counterargument of the violation of the Collatz hypothesis, but a universal characteristic of transformations of natural numbers by the 3n + 1 algorithm. A recurrent relationship is established between the parameters of the sequence of Collatz transformations of an arbitrary pair of natural numbers n and 2n.
Закономірності формування послідовностей 3n+1 перетворень як аргумент підтвердження гіпотези Коллатца
Keywords: гіпотеза Коллатца; послідовність; перетворення 3n+1; натуральні числа; Collatz conjecture; recurrent sequence; transformation 3n + 1; natural numbers